A linear method to extract diode model parameters of solar panels from a single I–V curve. (April 2015) - Lim, Li Hong Idris; Ye, Zhen; Ye, Jiaying; Yang, Dazhi; Du, Hui
Abstract: The I – V characteristic curve is very important for solar cells/modules being a direct indicator of performance. But the reverse derivation of the diode model parameters from the I – V curve is a big challenge due to the strong nonlinear relationship between the model parameters. It seems impossible to solve such a nonlinear problem accurately using linear identification methods, which is proved wrong in this paper. By changing the viewpoint from conventional static curve fitting to dynamic system identification, the integral-based linear least square identification method is proposed to extract all diode model parameters simultaneously from a single I – V curve. No iterative searching or approximation is required in the proposed method. Examples illustrating the accuracy and effectiveness of the proposed method, as compared to the existing approaches, are presented in this paper. The possibility of real-time monitoring of model parameters versus environmental factors (irradiance and/or temperatures) is also discussed. Highlights: A linear method of extracting the internal diode model parameters from the I – V characteristic curve for solar cells. The reverse derivation of diode model parameters is a big challenge due to the nonlinear relationship between the parameters. The integral-based linear least square identification method is proposed to extract all parameters simultaneously from a I – V curve. No iterative searching or approximation is required in the proposed method. Real life examples are provided to illustrate the accuracy and effectiveness of the proposed method.